THE FACTORS ENDANGERING THE SOCIALIZATION PROCESS OF JUNIOR SCHOOLCHILDREN (Education in the 21st Century, 2023)
The factors endangering the socialization process of junior schoolchildren emerge from the very first days of school life, Tutoring is one of the obvious dangers, on which the main emphasis is put in this article, It is obvious that the tutor cannot create the social environment and learning setting that is necessary for the effective socialization of a child, so the phenomenon of tutoring is one of the main reasons of education crisis, especially if it is universal. One of the factors hindering the socialization of junior schoolchildren is the fear of the teacher and assessment, which are psychological conditions that accompany the child every day and eventually turn into psychological complexes, significantly hindering his/her socialization. The role and significance of family as a core or small model of society are irreplaceable in terms of forming the social skills of junior schoolchildren. First, the junior schoolchildren learn the major part of the rules of social behaviour at home and then they continue that process at school. Unfortunately, in recent years, there has been a significant shortage of nuclear families in our country. Some fathers and mothers live abroad. Homework has become one of the main factors that endangers the process of socialization of junior schoolchildren. The schoolchildren strengthen the knowledge that they gain at school by doing their homework. In this way, they apply their knowledge in practice. Nowadays, the junior schoolchildren and their parents complain that the homework assigned by the teachers is really difficult. We also touch upon other factors that endanger the socialization process of junior schoolchildren in the article.
Keywords: socialization; primary school; system; tutoring; educational process; tutor; social process; behaviour change